Digital Humanities in Health Care: Exploring Behavioral Transformation through Literary Analysis of Franz Kafka’s Tale - Akuma Ifeanyichukwu; Vina Ravi Vaswani (Archives of Medicine and Health Sciences)
This article centers on addressing new challenges that, if given enough attention, will enrich the quality of healthcare delivery in the future. It employs the lens of digital humanities (DHs) to describe the implications of Franz Kafka’s tale in palliative and end-of-life care. Focusing on the DH approach to The Hunter Gracchus from the perspective of the digital world, DHs and behavioral transformation, traditional humanities, and behavioral change, and implications of the hunter Gracchus’s story, on the provision of medical care services. Highlighting the significance of emotional competence for healthcare professionals, encouraging the need to build competency via self-reflection, empathy, and understanding factors that may influence patients’ health and well-being to provide a broader perspective on patients’ experiences.